1990
DOI: 10.1055/s-2007-1004906
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Geriatric Patients for Thyroid Dysfunction with Thyrotropin-Releasing-Hormone Test, Sensitive Thyrotropin and Free Thyroxine Estimation

Abstract: Hospitalized geriatric patients (N = 354) from an iodine-deficient area were screened with sensitive thyrotropin (TSH), free and total thyroxine (FT4, T4) and total triiodothyronine (T3) to determine the occurrence rate of clinical and subclinical thyroid dysfunction. The diagnostic value of the tests was compared to each other and to that of the thyrotropin-releasing-hormone test (TRH-test) in order to find the optimal first line screening test in geriatric patients. Clinical hyperthyroidism was found in 13, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
0
11
0
4
Order By: Relevance
“…Only one third (34.8%) of the elderly with high TSH levels in our sample had elevated serum TSH values and low serum free T4 values. This showed that the serum TSH value was a more sensitive screening test of thyroid deficiency in the elderly than the serum T4 value [6,23]. Among those with overt hypothyroidism, the prevalence in women was higher than in men.…”
Section: Discussionmentioning
confidence: 94%
“…Only one third (34.8%) of the elderly with high TSH levels in our sample had elevated serum TSH values and low serum free T4 values. This showed that the serum TSH value was a more sensitive screening test of thyroid deficiency in the elderly than the serum T4 value [6,23]. Among those with overt hypothyroidism, the prevalence in women was higher than in men.…”
Section: Discussionmentioning
confidence: 94%
“…Alguns autores concordam que, com a idade, ocorra uma diminuição dos níveis séricos de T3, T4 e FT4 (9,14,(18)(19)(20)(21)(22)(23)25,26), enquanto para outros estes se mantém inalterados (14,23,24,27) com o envelhecimento. Níveis elevados (4,8,14) de TSH, baixos (15)(16)(17) ou inalterados (18) já foram descritos na população idosa.…”
Section: Introductionunclassified
“…TSH is a sensitive and specific screening test for hypothyroidism and has high predictive value (34). However, the lack of direct measurement of thyroid hormone levels makes it difficult to make inferences concerning possible effects of either sub-clinical hypo thyroidism or sub-clinical hyper thyroidism on cognitive function.…”
Section: Discussionmentioning
confidence: 99%